Penelitian Studi Pustaka Peran Media Sosial terhadap Karakter Mahasiswa - Muhammad Noval Ramadhan; Brian Pratana Hia (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Social media is now the first tool of interaction between humans with a very large number of users worldwide. The potential of social media to spread information in a short time and on a wider scale has affected many areas of life, especially in the process of forming individual personalities. This study examines the effects of social media on the character of college or university students, both for good and bad. On the one hand, it is noted that social media helps build bonds between people and helps in broadening one's perspective and even supports personal growth through social interaction in a positive way. However, on the other hand, social media also shows the potential to create social anxiety, social pressure, and identity issues due to social comparison and exposure to negative content. College students, who are in the stage of finding their identity, become easy targets for the influence of social media. In the right way, this media can be used to encourage them in forming positive characters. This study argues for the need for better digital literacy and the use of wise social media strategies to maintain high positive effects and low negative impacts.